2019
DOI: 10.2139/ssrn.3346759
|View full text |Cite
|
Sign up to set email alerts
|

Fraudulent Financial Reporting and the Consequences for Employees

Abstract: We examine employment effects, such as wages and employee turnover, before, during, and after periods of fraudulent financial reporting. To analyze these effects, we combine U.S. Census data with SEC enforcement actions against firms with serious misreporting ("fraud"). We find, compared to a matched sample, that fraud firms' employee wages decline by 9% and the separation rate is higher by 12% during and after fraud periods. Employment growth at fraud firms is positive during fraud periods and negative afterw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 106 publications
2
16
0
Order By: Relevance
“…In sum, my findings suggest that wage theft precedes financial misconduct. This result is consistent with Choi and Gipper (2019), who find that lower-paid employees' wages decline significantly in the years immediately preceding financial fraud; the results in Table 8 suggest one mechanism (wage theft) by which this decline occurs.…”
Section: Wage Theft and Financial Misconductsupporting
confidence: 89%
“…In sum, my findings suggest that wage theft precedes financial misconduct. This result is consistent with Choi and Gipper (2019), who find that lower-paid employees' wages decline significantly in the years immediately preceding financial fraud; the results in Table 8 suggest one mechanism (wage theft) by which this decline occurs.…”
Section: Wage Theft and Financial Misconductsupporting
confidence: 89%
“…After the public revelation of fraud, we do not find significant differences in subsequent employment between the non‐implicated and non‐fraud CFOs through two years after the SEC's first AAER. These results extend prior literature by revealing that while at‐fault executives often face compensation penalties (Hoitash et al 2012; Choi and Gipper 2021) and limited employment opportunities (Desai et al 2006; Karpoff et al 2008), non‐implicated CFOs enjoy better employment opportunities than non‐fraud CFOs until the public revelation of fraud.…”
Section: Introductionsupporting
confidence: 83%
“…The results support this inference, revealing compensation penalties for these professionals. Finally, Choi and Gipper (2021) focus on low‐wage employees who are unlikely to have been associated with fraudulent financial reporting, showing that they still suffer wage detriments and heightened turnover.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on misreporting, which is a type of occupational fraud that is defined as the managers' action of intentionally withholding or misrepresenting information (Chong & Wang, 2019;Keil & Robey, 2001). Prior studies have suggested that misreporting can lead to negative consequences for an organization (e.g., Choi & Gipper, 2019;Gao & Jia, 2021;Karpoff et al, 2008;Smith et al, 2009). 1 For example, Smith et al, (2009, p. 577) suggest that "without complete and accurate status information, a project manager's ability to monitor progress, allocate resources effectively, and detect and respond to problems is greatly diminished, and this can lead to impaired project performance."…”
Section: Introductionmentioning
confidence: 99%